2021
DOI: 10.1016/j.ebiom.2021.103429
|View full text |Cite
|
Sign up to set email alerts
|

TCR repertoire diversity in Multiple Sclerosis: High-dimensional bioinformatics analysis of sequences from brain, cerebrospinal fluid and peripheral blood

Abstract: Background: T cells play a key role in the pathogenesis of multiple sclerosis (MS), a chronic, inflammatory, demyelinating disease of the central nervous system (CNS). Although several studies recently investigated the T-cell receptor (TCR) repertoire in cerebrospinal fluid (CSF) of MS patients by high-throughput sequencing (HTS), a deep analysis on repertoire similarities and differences among compartments is still missing. Methods: We performed comprehensive bioinformatics on high-dimensional TCR Vb sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…We calculated the degree of each node in the network and plotted the degree distribution for all the repertoires in each of the three groups (pre-ART, post-ART, control). Previous studies have shown that naïve TRB repertoires exhibit an exponential degree distribution curve dominated by many-to-many interactions in the T-cell network ( 34 , 35 ). This has been attributed to the increased diversity typically observed in naïve repertoires, which results in a higher likelihood of finding sequences with an edit distance of one.…”
Section: Resultsmentioning
confidence: 99%
“…We calculated the degree of each node in the network and plotted the degree distribution for all the repertoires in each of the three groups (pre-ART, post-ART, control). Previous studies have shown that naïve TRB repertoires exhibit an exponential degree distribution curve dominated by many-to-many interactions in the T-cell network ( 34 , 35 ). This has been attributed to the increased diversity typically observed in naïve repertoires, which results in a higher likelihood of finding sequences with an edit distance of one.…”
Section: Resultsmentioning
confidence: 99%
“…MS was traditionally considered a T-cell-mediated autoimmune disorder, based on preclinical data from animal models of the disease (experimental autoimmune encephalomyelitis—EAE) and evidence for T-cell infiltration in inflammatory lesions and normal-appearing white matter of autoptic and biopsy CNS specimens from affected individuals, with an association between CD8+ T cells number and axonal damage [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Furthermore, the identification of expanded T-cell clones in the brain parenchyma, cerebrospinal fluid (CSF), and peripheral blood of MS patients detected using T-cell receptor (TCR) analyses reinforced the hypothesis that inflammatory infiltrates were constituted by pathogenetic expanded T-cell clones reactive to myelin antigens [ 13 , 14 , 15 , 16 ]. Circulating CD4+ T cells from MS patients were indeed demonstrated to recognise myelin basic protein (MBP), proteolipid protein (PLP), and myelin oligodendrocyte glycoprotein (MOG), even if the same phenomenon was also observed in healthy individuals; evidence regarding potential differences between these groups in frequency and avidity of cell interactions is conflicting [ 17 , 18 ].…”
Section: Insights Into Ms Pathogenesis: Onset Of Autoimmunitymentioning
confidence: 91%
“…These modelling algorithms have the potential to scrutinize TCR repertoires of patients with autoimmune disease for autoreactive clones. Recently, highdimensional TCR sequencing analysis has assessed clusters of clones in the CSF and peripheral blood of MS patients, confirming the effect of MS on the TCR clonal profile (41). MS is presumed to arise as a result of auto-reactive T-cells (42), which are likely to escape negative selection in the thymus and then become activated following interaction with undefined environmental factors.…”
Section: Introductionmentioning
confidence: 95%